Reverse transcription multiplex PCR for differentiation between polio- and enteroviruses from clinical and environmental samples. - Egger, D (1995)
For the rapid detection of polioviruses and their differentiation from nonpoliovirus enteroviruses, we developed a protocol in which clinical or environmental specimens are first inoculated onto cell cultures in tubes. After overnight incubation, the cultures are subjected to reverse transcription multiplex PCR with a primer pair which detects all enteroviruses (T. Hyypiä, P. Auvinen, and M. Maaronen, J. Gen. Virol. 70:3261-3268 1989) and two newly designed primer pairs specific for all 36 poliovirus strains tested. The PCR products can unequivocally be identified by their lengths in agarose gels, whereas the genetic heterogeneity of the poliovirus strains precludes identification by back-hybridization with internal probes. The proposed protocol is highly insensitive to the inhibitory effects of substances in the sample (stool, sewage). It allows for the detection of polioviruses and for polioviruses to be distinguished from nonpoliovirus enteroviruses within 24 h, and it allows for the concomitant isolation of a viable strain suitable for further typing.